Surface protonation amplifies carbon nitride nanosheet-induced phospholipid extraction: Mechanistic insights into enhanced cytotoxicity - Yiping Feng; Jiayong Lao; Jingchuan Xue (Environmental Chemistry and Ecotoxicology)
The transformation of graphitic carbon nitride (g-C3N4) in biological and environmental systems can significantly alter its properties and toxicity, posing potential risks to human health and biological systems. This study systematically examines the cytotoxicity evolution of protonated carbon nitride (p-C3N4) toward red blood cells and elucidates its underlying mechanisms. Hemolysis assays revealed that p-C3N4 exhibits enhanced phospholipid membrane-rupturing capabilities compared to pristine g-C3N4, with absence of significant lipid peroxidation detected via malondialdehyde assays. Surface characterization revealed that protonation reduces the net negative charge of carbon nitride, thereby increasing its affinity with phospholipid membranes. Molecular docking simulations identified that the interactions between p-C3N4 and phospholipid molecules are governed by electrostatic and hydrophobic forces, as well as hydrogen bonding with oxygen-containing functional groups. Molecular dynamics simulations further revealed that larger oxygen-bearing macropores on p-C3N4 allow for tight and specific binding with phospholipid headgroups, facilitating efficient lipid extraction and intensifying membrane disruption. These findings provide critical insights into the cytotoxic changes that carbon nitride materials may undergo during transformations, emphasizing the importance of careful application and disposal of them in biomedical and environmental contexts. Furthermore, this work highlights opportunities to mitigate associated risks or use surface protonation for enhanced functionality in carbon nitride-based technologies.